2016
DOI: 10.1093/ntr/ntw199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-Week Use of Reduced-Nicotine Content Cigarettes in Smokers With and Without Elevated Depressive Symptoms

Abstract: Background: The FDA recently acquired regulatory authority over tobacco products, leading to renewed interest in whether reducing the nicotine content of cigarettes would reduce tobacco dependence in the United States. Given the association between depressive symptoms and cigarette smoking, it is important to consider whether smokers with elevated depressive symptoms experience unique benefits or negative consequences of nicotine reduction. Methods: In this secondary analysis of a randomized clinical trial tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 54 publications
5
52
0
Order By: Relevance
“…Furthermore, smokers with psychiatric disorders would likely experience similar benefits related to their cigarette use (ie, reduced smoking, reduced dependence and increased quitting). For example, participants with elevated baseline symptoms of depression (CES-D ≥16) displayed similar reductions in nicotine exposure, cigarettes per day and dependence as participants with fewer symptoms of depression 39. Nevertheless, given the potential concerns the use of VLNC cigarettes might present in smokers with psychiatric comorbidities,21 37 research is underway and likely to provide more definitive evidence within the next few years, including studies of smokers with affective disorders, schizophrenia, attention deficit hyperactivity disorder and current opioid abuse (see online supplementary materials).…”
Section: Common Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, smokers with psychiatric disorders would likely experience similar benefits related to their cigarette use (ie, reduced smoking, reduced dependence and increased quitting). For example, participants with elevated baseline symptoms of depression (CES-D ≥16) displayed similar reductions in nicotine exposure, cigarettes per day and dependence as participants with fewer symptoms of depression 39. Nevertheless, given the potential concerns the use of VLNC cigarettes might present in smokers with psychiatric comorbidities,21 37 research is underway and likely to provide more definitive evidence within the next few years, including studies of smokers with affective disorders, schizophrenia, attention deficit hyperactivity disorder and current opioid abuse (see online supplementary materials).…”
Section: Common Questionsmentioning
confidence: 99%
“…Smokers with psychiatric disorders commonly quit smoking with standard treatments and experience little deterioration or even improvements in their psychiatric symptoms 37 38. Initial studies of smokers with elevated baseline symptoms of depression (Center for Epidemiological Studies—Depression Scale, CES-D, ≥16) or schizophrenia suggest that use of VLNC cigarettes does not exacerbate their symptoms 39 40. Furthermore, smokers with psychiatric disorders would likely experience similar benefits related to their cigarette use (ie, reduced smoking, reduced dependence and increased quitting).…”
Section: Common Questionsmentioning
confidence: 99%
“…The 5.2 mg/g condition was excluded due to inconsistent effects in the overall sample (e.g., compared to 15.8 mg/g, it resulted in similar CPD but reduced nicotine exposure (Donny et al, 2015)), and to remain consistent with prior secondary analyses (Tidey et al, In press). This lead to a sample size of n=717 for this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of baseline depressive symptoms, participants randomized to VLNC cigarettes had lower smoking rates, nicotine intake, nicotine dependence, and craving at week 6 post-randomization than those assigned to normal-nicotine cigarettes. In those with higher baseline depressive symptoms, VLNC cigarettes were associated with lower week 6 depressive symptoms than those assigned to normal-nicotine cigarettes [103]. There are a few smaller studies also supporting use of VLNC cigarettes for reducing exposure and harm [104,105], and a protocol has been published for evaluation specifically in smokers with mood and/or anxiety disorders [106].…”
Section: Approaches To Tobacco Harm Reductionmentioning
confidence: 99%
“…Relative to the standard cigarettes, for both smokers with and without schizophrenia, when smoking the VLNC, their puff duration increased, while the time between puffs decreased as did total puffs and total cigarette volume. The authors concluded that acute VLNC cigarette use did not increase smoking in those with schizophrenia [103]. A 2010 randomized semi-blinded study examined whether varying lower nicotine content cigarettes were associated with compensatory smoking behavior and found that they do not.…”
Section: Approaches To Tobacco Harm Reductionmentioning
confidence: 99%